2019
DOI: 10.1007/s00442-019-04423-y
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of soil waterlogging on herbaceous and woody plant communities in a Neotropical savanna

Abstract: The impacts of soil properties and fire regime on Neotropical savannas are wellknown, but the importance of hydrological regime for plant species assembly has received less attention. Here we assessed changes in diversity patterns of herbaceous and woody communities along a water table gradient in a fire-excluded Neotropical savanna. We found that increased waterlogging of soils was associated with declines in both herbaceous and woody species richness. Woody species richness decreased once the water table dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 93 publications
(116 reference statements)
0
12
0
Order By: Relevance
“…When the climate was drying, a slight warming and drying trend was conducive to the growth of perennial, warm-season plants (Ford, 2003), thus promoting the increase in FHVC. It has been reported that an absence of or a minimum amount of stalk (skeletal) organs in herbs was compensated by an increase in root mass, providing a herb vegetation advantage in the competition for moisture and domination in the steppe zone (Abaturov, 2015). However, the increasing trend of FHVC driven by temperature change or precipitation change was almost too slight to be captured, which indicated that other driving forces of the variation in FHVC were greater.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the climate was drying, a slight warming and drying trend was conducive to the growth of perennial, warm-season plants (Ford, 2003), thus promoting the increase in FHVC. It has been reported that an absence of or a minimum amount of stalk (skeletal) organs in herbs was compensated by an increase in root mass, providing a herb vegetation advantage in the competition for moisture and domination in the steppe zone (Abaturov, 2015). However, the increasing trend of FHVC driven by temperature change or precipitation change was almost too slight to be captured, which indicated that other driving forces of the variation in FHVC were greater.…”
Section: Discussionmentioning
confidence: 99%
“…The increase of FWVC with associated FHVC decrease mostly distributed in areas getting both wetter and drier while warmer, but the indicated driving mechanisms may be different. On-the -one-hand, the humid climate enhanced the competitiveness of woody plants through providing the environment for the growth of woody plants, for instance, the skeletal organs (tree stems) of woody plants made more efficient use of light energy (Abaturov, 2015). On-the-other-hand, the interaction of humid climate with other factors could also promote the woody encroachment.…”
Section: Discussionmentioning
confidence: 99%
“…The loose material originates from various geomorphological processes that work in the erosional zone and the residual zone [54]. Due to the extremely high soil water content, the depositional zones need to be controlled with plants that minimize the intensity of gully erosion, soil cracks, landslides, and soil creeps [55]. The high water content can be maintained by cultivating high water consumption plants such as bamboo [56][57][58], banana [59,60], sugar palm [61,62], and coconut [63].…”
Section: Discussionmentioning
confidence: 99%
“…We quantified soil variables commonly associated as indicators of waterlogging (i.e., soil organic matter, Junk et al 2014), soil water-holding capacity in well-drained soils (proportion of clay soil particles) and soil fertility (i.e., soil base saturation) (Ellis and Mellor 1995). We expect that, although adjacent to the other vegetation types, the moist grassland will have a distinct flora since soil waterlogging selects species adapted to this condition (Cianciaruso and Batalha 2009;Silva et al 2018;de Xavier et al 2019). On the other hand, the shrub grassland and the savanna will have a higher similarity of herbaceous-shrub species as both are located on well-drained soil (Munhoz and Felfili 2007).…”
Section: Introductionmentioning
confidence: 99%